PENGARUH PEMANFAATAN PERPUSTAKAAN SEKOLAH, BUDAYA MEMBACA, KOMPETENSI GURU, TERHADAP HASIL BELAJAR EKONOMI - Achmad Rifa'i; Pujiati Pujiati; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2015)
This study aims to determine the effect of the use of the school library, reading culture, and students perception of teacher competence on learning outcomes Economy class XI IPS at SMA Negeri 1 Trimurjo academic year 2014/2015. The method used in this research is descriptive approach verification ex post facto and surveys. The population in this study amounted to 63 students with a sample of 54 students using simple random sampling technique. Data were collected through questionnaires and observation. Based on the analysis of data obtained as follows: (1) there is an influence the use of the school library to the learning outcomes of Economics, (2) there is an influence of reading culture on learning outcomes Economic, (3) there is an influence students' perception of teacher competence on learning outcomes Economics, and (4) there is an influence of the use of the school library, reading culture, and student perceptions of teacher competence on learning outcomes Economics.Penelitian ini bertujuan untuk mengetahui pengaruh pemanfaatan perpustakaan sekolah, budaya membaca, dan persepsi siswa tentang kompetensi guru terhadap hasil belajar Ekonomi siswa kelas XI IPS SMA Negeri 1 Trimurjo Tahun Pelajaran 2014/2015. Metode yang digunakan dalam penelitian ini adalah deskriptif verifikatif dengan pendekatan ex post facto dan survey. Populasi dalam penelitian ini berjumlah 63 siswa dengan sampel 54 siswa menggunakan teknik simple random sampling. Data yang terkumpul melalui angket dan obsevasi. Berdasarkan analisis data diperoleh hasil sebagai berikut: (1) terdapat pengaruh pemanfaatan perpustakaan sekolah terhadap hasil belajar Ekonomi, (2) terdapat pengaruh budaya membaca terhadap hasil belajar Ekonomi, (3) terdapat pengaruh persepsi siswa tentang kompetensi guru terhadap hasil belajar Ekonomi, dan (4) terdapat pengaruh pemanfaatan perpustakaan sekolah, budaya membaca, dan persepsi siswa tentang kompetensi guru terhadap hasil belajar Ekonomi.Kata kunci: belajar, kompetensi, membaca, perpustakaan